Raw material composition for ceramic tile joint mixture, ceramic tile joint mixture and preparation method of ceramic tile joint mixture
By using specific combinations of epoxy resins and modified amine-based epoxy curing agents, the problem of insufficient compression and bonding capabilities of existing tile fillers is solved, and the service life and safety of the existing epoxy resin is achieved, and the navigation effect is provided with high brightness.
Patent Information
- Application Number
- CN202411821773.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-11
AI Technical Summary
Under the influence of strong external forces or long-term natural environmental factors, existing ceramic tile joint fillers are prone to problems such as drying and cracking, tiles falling off, short service life, and have poor compressive resistance and bonding and shearing ability.
A raw material composition for ceramic tile joint filler is adopted, which includes combination A and combination B. Combination A contains epoxy resin, nano-calcium carbonate, defoaming agent, active diluent and luminescent powder. Combination B contains modified amine-based epoxy curing agent, nano-calcium carbonate, thixotropic agent, accelerator, toughening agent, defoaming agent, luminescent powder and pigment. Ceramic tile joint filler is prepared by stirring and mixing.
It improves the viscosity of tile caulking agent, enhances its compressive resistance and bonding and shearing ability, extends the service life of tile, and provides high afterglow brightness in darker light to help navigation.
Smart Images

Figure BDA0005183270880000111 
Figure BDA0005183270880000131 
Figure BDA0005183270880000141
Abstract
Description
Technical Field
[0001] The invention relates to the field of tile caulking agents, and in particular to a raw material composition for tile caulking agents, a tile caulking agent and a preparation method thereof. Background Art
[0002] Ceramic tiles are commonly used as floor and wall decoration materials in indoor and outdoor decoration. A very important process during installation is leaving gaps. Leaving gaps not only helps to cope with volume changes caused by changes in temperature and humidity, compensate for construction errors, enhance tile adhesion, prevent hollowing and falling off, but also improves the durability and aesthetics of tile paving.
[0003] Tile grout is used for gap decoration. Its performance is constantly optimized and its main development has gone through the following stages:
[0004] The first generation: white cement caulking agent, is the earliest caulking material. Its main component is white cement. It is not stain-resistant and has been eliminated.
[0005] The second generation: cement-based caulking agent is a traditional caulking material that has been used for many years and is usually filled by masons directly after laying tiles. The advantage is low cost, but poor waterproof and mildew resistance.
[0006] The third generation: Resin caulking agent, usually a two-component product, consists of resin pigment, curing agent and solvent. It is mildew-proof and easy to clean.
[0007] Existing caulking agents are mainly used to fill the gaps between decorative materials such as tiles to prevent water infiltration and mold growth, and to keep the walls and floors beautiful and clean. However, as people's demand for durability and safety of home decoration continues to increase, some shortcomings of existing caulking agents have gradually emerged.
[0008] Existing caulking agents are prone to drying and cracking, tile falling off, and short service life under the influence of strong external forces or long-term natural environmental factors. This not only reduces the aesthetics of the caulking agent, but also the falling of tiles from high places can cause serious harm to human life safety.
[0009] CN118064091A discloses a caulking agent for use in the gaps of bathroom tiles, comprising component A and component B: component A comprises the following raw materials in parts by weight: 10-25 parts of fatty alcohol-modified bisphenol A epoxy resin, 20-30 parts of epoxy resin, 20-30 parts of filler A, 6-10 parts of pigment, 0.5-1 part of plasticizer, and 0.1-1 part of defoamer; component B comprises the following raw materials in parts by weight: 30-50 parts of modified amine curing agent, 20-30 parts of filler B, 1-3 parts of toughening agent, 1-3 parts of antibacterial agent, and 0.5-3 parts of dispersant and / or diluent. Although the caulking agent can adapt to changes in temperature and humidity, has excellent resistance to moisture and heat and antibacterial effects, has strong adsorption combined with tile materials, can fully fill the gaps of tiles, and ensure the decorative effect, it does not have strong compressive resistance and bonding shearing ability, and is easy to crack and fall off under the action of external forces.
[0010] Therefore, there is an urgent need for a tile caulking agent with high viscosity, strong compressive resistance and strong bonding shearing ability to solve this defective situation. Summary of the invention
[0011] The purpose of the present invention is to overcome the problems of poor compressive strength, poor bonding shearing ability and low viscosity of the ceramic joint agent provided by the prior art.
[0012] In order to achieve the above-mentioned object, the first aspect of the present invention provides a raw material composition for tile grout, wherein the composition contains a combination A and a combination B in a weight ratio of 1:0.8-1.2;
[0013] Based on the total mass of the A combination, the A combination contains: 80-90wt% epoxy resin, 5-10wt% nano calcium carbonate, 1-3wt% defoamer, 1-10wt% active diluent, and 1-10wt% luminous powder;
[0014] Based on the total mass of the B combination, the B combination contains: 70-80wt% of modified amine epoxy curing agent, 5-10wt% of nano calcium carbonate, 1-3wt% of thixotropic agent, 1-3wt% of accelerator, 1-10wt% of toughening agent, 1-3wt% of defoaming agent, 1-10wt% of luminous powder, and 0-10wt% of pigment;
[0015] In the combination A, the epoxy resin is a combination of bisphenol A epoxy resin and hydrogenated bisphenol A epoxy resin, and the amounts of the bisphenol A epoxy resin and the hydrogenated bisphenol A epoxy resin are such that the epoxy equivalent of the epoxy resin in the combination A is 180-190 g / mol;
[0016] In the B combination, the active hydrogen equivalent of the modified amine epoxy curing agent is 170-180 g / mol;
[0017] In the combination A and the combination B, the average volume diameter of the nano-calcium carbonate particles is 0.01 μm-0.1 μm.
[0018] The second aspect of the present invention provides a method for preparing a tile grout, which is carried out using the components in the composition described in the first aspect, comprising:
[0019] (1) Preparation of the first component and the second component:
[0020] Under stirring conditions, the components in combination A are first mixed to obtain a first component; and,
[0021] Under stirring conditions, the components in combination B are mixed for a second time to obtain a second component;
[0022] (2) The first component and the second component are mixed and contacted to obtain the tile grout.
[0023] The third aspect of the present invention provides a tile grout prepared by the method described in the second aspect.
[0024] The tile caulking agent provided by the present invention has the characteristics of high viscosity, strong compressive resistance and strong bonding shearing ability, can effectively enhance the adsorption capacity of tiles, reduce cracking and falling off under the action of external forces, and extend the service life of tiles.
[0025] In addition, the tile caulking agent provided by the present invention has the performance of high afterglow brightness while ensuring excellent mechanical properties, and can play the role of marking and prompting in dark places, helping people to find the path more easily or avoid collisions. DETAILED DESCRIPTION
[0026] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0027] It should be noted that, in various aspects of the present invention, for the same components or terms in various aspects, the present invention is described only once in one aspect without repeated description, which should not be understood by those skilled in the art as a limitation of the present invention.
[0028] As mentioned above, the first aspect of the present invention provides a raw material composition for tile grout, the composition comprising a combination A and a combination B in a weight ratio of 1:0.8-1.2;
[0029] Based on the total mass of the A combination, the A combination contains: 80-90wt% epoxy resin, 5-10wt% nano calcium carbonate, 1-3wt% defoamer, 1-10wt% active diluent, and 1-10wt% luminous powder;
[0030] Based on the total mass of the B combination, the B combination contains: 70-80wt% of modified amine epoxy curing agent, 5-10wt% of nano calcium carbonate, 1-3wt% of thixotropic agent, 1-3wt% of accelerator, 1-10wt% of toughening agent, 1-3wt% of defoaming agent, 1-10wt% of luminous powder, and 0-10wt% of pigment;
[0031] In the combination A, the epoxy resin is a combination of bisphenol A epoxy resin and hydrogenated bisphenol A epoxy resin, and the amounts of the bisphenol A epoxy resin and the hydrogenated bisphenol A epoxy resin are such that the epoxy equivalent of the epoxy resin in the combination A is 180-190 g / mol;
[0032] In the B combination, the active hydrogen equivalent of the modified amine epoxy curing agent is 170-180 g / mol;
[0033] In the combination A and the combination B, the average volume diameter of the nano-calcium carbonate particles is 0.01 μm-0.1 μm.
[0034] Preferably, based on the total mass of the combination A, the combination A contains: 80-85wt% epoxy resin, 5-10wt% nano calcium carbonate, 1-3wt% defoaming agent, 2-8wt% active diluent, and 5-10wt% luminous powder.
[0035] Preferably, based on the total mass of the B combination, the B combination contains: 75-80wt% modified amine epoxy curing agent, 5-10wt% nano calcium carbonate, 1-3wt% thixotropic agent, 2-3wt% accelerator, 2-6wt% toughening agent, 1-3wt% defoaming agent, 5-10wt% luminous powder, and 0-10wt% pigment.
[0036] More preferably, based on the total mass of the B combination, the B combination contains: 75-80wt% of modified amine epoxy curing agent, 5-10wt% of nano calcium carbonate, 1-3wt% of thixotropic agent, 2-3wt% of accelerator, 1-10wt% of toughening agent, 1-3wt% of defoaming agent, 5-10wt% of luminous powder, and 5-10wt% of pigment.
[0037] According to a preferred specific implementation, based on the total mass of the A combination, the A combination contains: 80-85wt% epoxy resin, 5-10wt% nano calcium carbonate, 1-3wt% defoamer, 2-8wt% reactive diluent, 5-10wt% luminous powder; based on the total mass of the B combination, the B combination contains: 75-80wt% modified amine epoxy curing agent, 5-10wt% nano calcium carbonate, 1-3wt% thixotropic agent, 2-3wt% accelerator, 2-6wt% toughening agent, 1-3wt% defoamer, 5-10wt% luminous powder, 0-10wt% pigment. The inventors found that under this preferred condition, the tile caulking agent provided by the present invention has a higher viscosity and stronger compressive strength and bonding shearing ability.
[0038] Preferably, in the combination A, the weight ratio of the bisphenol A epoxy resin to the hydrogenated bisphenol A epoxy resin in the epoxy resin is 2-3:1.
[0039] Particularly preferably, in the combination A, the bisphenol A epoxy resin is CYD-128 produced by Baling Petrochemical, and the hydrogenated bisphenol A epoxy resin is XY518 produced by Wuhan Jiufengyun New Materials Co., Ltd.
[0040] It should be noted that, in the combination A and the combination B, the types of nano-calcium carbonate may be the same or different, and each may be independently selected from nano-calcium carbonate having an average particle diameter of 0.01 μm to 0.1 μm.
[0041] Particularly preferably, the nano calcium carbonate is NEOLIGHT SP provided by Takehara Chemical.
[0042] It should be noted that, in the combination A and the combination B, the types of luminous powder may be the same or different, and each may be independently selected from yellow-green and / or blue-green luminous powder.
[0043] Particularly preferably, in the combination A and the combination B, the luminous powder is yellow-green luminous powder and / or blue-green luminous powder, and the average volume diameter of the particles is ≤50 μm. Exemplarily, the yellow-green luminous powder (surface modified) and blue-green luminous powder (no surface modified) are from Foshan Juliang Optical Materials Co., Ltd.
[0044] Preferably, in the combination A, the active diluent is at least one of 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and polypropylene glycol diglycidyl ether.
[0045] Particularly preferably, in the combination A, the active diluent is 1,6-hexanediol diglycidyl ether. The inventors of the present invention have found in their research that, under this preferred condition, the tile grout provided by the present invention has a higher viscosity and stronger compression resistance and bonding shear ability.
[0046] More preferably, in the combination A, the active diluent is LS-622 produced by Hubei Green Home Materials Technology Co., Ltd.
[0047] Preferably, in the combination B, the thixotropic agent is a polyamide solution. Particularly preferably, in the combination B, the thixotropic agent is at least one of a polyamide wax anti-settling agent, a polyamide wax micropowder thixotropic anti-settling agent, and a polyamide modified hydrogenated castor oil thixotropic agent.
[0048] Preferably, in the B combination, the accelerator is a tertiary amine accelerator. More preferably, in the B combination, the accelerator is at least one of 2,4,6-tris(dimethylaminomethyl)phenol, benzyldimethylamine, and o-hydroxybenzyldimethylamine. Particularly preferably, in the B combination, the accelerator is DMP-30 from Dongguan Tuoxin Composite Materials Co., Ltd.
[0049] Preferably, in the combination B, the toughening agent is an amino-terminated liquid nitrile rubber. More preferably, the number average molecular weight of the amino-terminated liquid nitrile rubber is 3000-4000. Particularly preferably, in the combination B, the toughening agent of the present invention is provided by Huntsman 1300X21 ATBN model toughener.
[0050] Preferably, in the combination B, the modified amine epoxy curing agent is an addition amine, which is a reaction product of an amine curing agent and an epoxy resin or an epoxy reactive diluent. Particularly preferably, the modified amine epoxy curing agent can be a modified amine epoxy curing agent of model TX1113 provided by Dongguan Tuoxin Composite Materials Co., Ltd. The inventors found that in this preferred case, the tile caulking agent provided by the present invention has the advantages of greater viscosity and stronger compressive resistance and bonding shear ability.
[0051] As mentioned above, the second aspect of the present invention provides a method for preparing a tile grout, which is carried out using the components in the composition described in the first aspect, comprising:
[0052] (1) Preparation of the first component and the second component:
[0053] Under stirring conditions, the components in combination A are first mixed to obtain a first component; and,
[0054] Under stirring conditions, the components in combination B are mixed for a second time to obtain a second component;
[0055] (2) The first component and the second component are mixed and contacted to obtain the tile grout.
[0056] Preferably, in step (1), the operation of first mixing the components in combination A under stirring conditions comprises:
[0057] (S11) performing a first stirring treatment on a bisphenol A epoxy resin and a hydrogenated bisphenol A epoxy resin to obtain a material S11;
[0058] (S12) at a temperature of 40-50° C., subjecting the material S11 to a second stirring treatment with the nano-calcium carbonate in combination A, the defoaming agent in combination A, and the active diluent in combination A to obtain material S12; the temperature of T1 is 40-50° C.;
[0059] (S13) subjecting the material S12 and the luminous powder in combination A to a third stirring treatment to obtain the first component.
[0060] Preferably, in step (S11), the conditions of the first stirring treatment include: a stirring rate of 400-600 rpm.
[0061] Further preferably, in step (S12), the conditions of the second stirring treatment include: a stirring rate of 900-1000 rpm, a stirring time of 25-35 min, and a pressure ≥-0.09 MPa.
[0062] Preferably, in step (S13), the conditions of the third stirring treatment include: a stirring rate of 400-600 rpm and a stirring time of 10-20 min.
[0063] Preferably, in step (2), the operation of subjecting the components in combination B to a second mixing under stirring conditions comprises:
[0064] (S21) at a temperature of 45-50° C., the modified amine epoxy curing agent, the accelerator, the toughening agent, the defoaming agent in the combination B, and the nano-calcium carbonate in the combination B are subjected to a fourth stirring treatment to obtain material S21; the temperature T2 is 45-50° C.;
[0065] (S23) subjecting the material S21, the thixotropic agent, the luminous powder in the combination B, and the pigment optionally contained in the combination B to a fifth stirring treatment to obtain the second component.
[0066] Preferably, in step (S21), the conditions of the fourth stirring treatment include: a stirring rate of 900-1000 rpm, a stirring time of 25-35 min, and a pressure ≥-0.09 MPa.
[0067] More preferably, in step (S22), the conditions of the fifth stirring treatment include: a stirring rate of 400-600 rpm, and a stirring time of 10-20 min.
[0068] As mentioned above, the third aspect of the present invention provides a tile grout prepared by the method described in the second aspect.
[0069] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise specified, all the instruments and raw materials used are commercially available.
[0070] Bisphenol A epoxy resin: purchased from Baling Petrochemical, trade name CYD-128;
[0071] Hydrogenated bisphenol A epoxy resin: purchased from Wuhan Jiufengyun New Materials Co., Ltd., trade name XY518;
[0072] Epoxy resin-1: the weight ratio of bisphenol A epoxy resin and hydrogenated bisphenol A epoxy resin is 3:1, and the epoxy equivalent is 188 g / mol;
[0073] Epoxy resin-2: The weight ratio of bisphenol A epoxy resin and hydrogenated bisphenol A epoxy resin is 1:1, and the epoxy equivalent is 188 g / mol;
[0074] Nano calcium carbonate: the average volume diameter of the particles is 0.1 μm, purchased from Takehara Chemical, the trade name is NEOLIGHTSP;
[0075] Defoaming agent: purchased from Dongguan Tuoxin Composite Materials Co., Ltd., trade name TX6750;
[0076] Active diluent A: 1,6-hexanediol diglycidyl ether, purchased from Hubei Green Home Material Technology Co., Ltd., trade name LS-622;
[0077] Active diluent B: 1,4-butanediol diglycidyl ether, purchased from Guangzhou Ruishi Biotechnology Co., Ltd., trade name RS-1422;
[0078] Luminous powder A: yellow-green luminous powder, with an average volume diameter of 30 μm, purchased from Foshan Juliang Optical Materials Co., Ltd.
[0079] Luminous powder B: blue-green luminous powder, with an average volume diameter of 48 μm, purchased from Foshan Juliang Optical Materials Co., Ltd.
[0080] Modified amine epoxy curing agent A: active hydrogen equivalent is 175, purchased from Dongguan Tuoxin Composite Materials Co., Ltd., trade name TX1113;
[0081] Modified amine epoxy curing agent B: active hydrogen equivalent is 168, purchased from Huntsman Aradur5200 latent curing agent, trade name MDH;
[0082] Accelerator: 2,4,6-tris(dimethylaminomethyl)phenol, purchased from Dongguan Tuoxin Composite Materials Co., Ltd., trade name DMP-30;
[0083] Toughening agent: purchased from Huntsman Company, trade name 1300X21 ATBN;
[0084] Thixotropic agent: purchased from Dongguan Tuoxin Composite Materials Co., Ltd., trade name TX607;
[0085] Pigment: Noble silver powder, purchased from Jiangsu Belide New Materials Co., Ltd.
[0086] Vacuum degassing mixer: model ZYMC-350VS, purchased from Shenzhen Zhongyi Technology Co., Ltd.
[0087] Universal testing machine: Model CMT6000, purchased from Meters Industrial Systems (China) Co., Ltd.
[0088] Pull-out testing machine: Model LBY-VI, purchased from Beijing Tianyu Technology Co., Ltd.
[0089] Measuring balance: Model: ME3002T, purchased from Mettler-Toledo.
[0090] The following uses the provisions of JCT 547-2017 Ceramic Tile Adhesive Standard to test shear bond strength.
[0091] The compressive strength was tested using the provisions of the JCT 1004-2017 ceramic tile grout standard.
[0092] The stain resistance is tested using the provisions of JGT 463-2014 Standard for Artificial Quartz Slabs for Architectural Decoration.
[0093] The afterglow brightness is tested using the provisions of GBT 24981.2-2020 Test method for rare earth long afterglow phosphors Part 2: Relative brightness.
[0094] Example 1
[0095] This example is used to illustrate the preparation method of the tile caulking agent of the present invention (partial parameters are shown in Table 1), comprising:
[0096] (1) Preparation of the first component and the second component:
[0097] Under stirring conditions, the components in combination A are first mixed to obtain a first component. The first mixing operation includes:
[0098] (S11) performing a first stirring treatment on the epoxy resin at a rotation speed of 500 rpm to obtain a material S11;
[0099] (S12) subjecting the material S11 to a second stirring treatment with the active diluent in combination A, the defoaming agent in combination A, and the nano-calcium carbonate in combination A at 1000 rpm, -0.09 MPa, and temperature T1 to obtain material S12;
[0100] (S13) The material S12 and the luminous powder in combination A are subjected to a third stirring treatment at a rotation speed of 500 rpm to obtain the first component.
[0101] Under stirring conditions, the components in the B combination are mixed for the second time to obtain a second component. The second mixing operation includes:
[0102] (S21) performing a fourth stirring treatment on the modified amine epoxy curing agent, the accelerator, the toughening agent, the defoaming agent in the combination B, and the nano-calcium carbonate in the combination B at 1000 rpm, -0.09 MPa, and T2 temperature to obtain material S21;
[0103] (S23) The material S21 is subjected to a fifth stirring treatment with a thixotropic agent, the luminous powder in the combination B, and a pigment optionally contained in the combination B at a rotation speed of 500 rpm to obtain the second component.
[0104] (2) The first component and the second component are mixed and contacted to obtain the tile grout.
[0105] Unless otherwise specified, the remaining examples are carried out using the same process as Example 1, except that the formulations and process parameters used in each example are different. The formulations used are specifically shown in Table 1, and the process parameters used are specifically shown in Table 2.
[0106] Table 1
[0107]
[0108] Table 2
[0109] Example 1 Example 2 Example 3 First Mix Second stirring process T1 temperature / ℃ 50 40 50 Time / min 30 35 35 The third stirring treatment, time / min 15 20 20 Second Mix Fourth stirring process T2 temperature / ℃ 50 50 45 Time / min 30 35 25 Fifth stirring treatment, time / min 15 15 20
[0110] Example 4
[0111] This example is carried out by referring to the method of Example 1, except that during the preparation of the first component, an equal weight of epoxy resin-2 is used to replace the epoxy resin-1 in Example 1, and the remaining substances and amounts are the same as those in Example 1, to obtain a tile grout.
[0112] Example 5
[0113] This example is carried out by referring to the method of Example 1, except that, in the preparation process of the first component, an equal weight of active diluent B is used to replace the active diluent A in Example 1, and the remaining substances and amounts are the same as those in Example 1, to obtain a tile grout.
[0114] Comparative Example 1
[0115] This comparative example was carried out with reference to the method of Example 1, except that:
[0116] During the preparation of the first component, the amount of epoxy resin-1 in this comparative example was 70 g, and the amount of active diluent A was adjusted to 17 g (the total mass of the A combination was 100 g).
[0117] The dosage of the remaining substances is the same as that in Example 1 to obtain a tile grout.
[0118] Comparative Example 2
[0119] This comparative example was carried out with reference to the method of Example 1, except that:
[0120] In the preparation process of the first component, the amount of nano calcium carbonate in this comparative example is 1 g, and the amount of epoxy resin is adjusted to 88 g (the total mass of the A combination is 100 g);
[0121] During the preparation of the second component, the amount of nano calcium carbonate used in this comparative example is 1 g, and the amount of the modified amine epoxy curing agent is adjusted to 84 g (the total mass of the B combination is 100 g).
[0122] The dosage of the remaining substances is the same as that in Example 1 to obtain a tile grout.
[0123] Comparative Example 3
[0124] This comparative example was carried out with reference to the method of Example 1, except that:
[0125] During the preparation of the first component, no luminous powder was added in this comparative example, and the amount of epoxy resin-1 in combination A was adjusted to 89 g (the total mass of combination A was 100 g).
[0126] The dosage of the remaining substances is the same as that in Example 1 to obtain a tile grout.
[0127] Comparative Example 4
[0128] This comparative example was carried out with reference to the method of Example 1, except that:
[0129] During the preparation of the second component, no luminous powder was added in this comparative example, and the amount of modified amine epoxy curing agent in combination B was adjusted to 81 g (the total mass of combination B was 100 g).
[0130] The dosage of the remaining substances is the same as that in Example 1 to obtain a tile grout.
[0131] Comparative Example 5
[0132] This comparative example was carried out with reference to the method of Example 1, except that:
[0133] During the preparation of the second component, an equal weight of modified amine epoxy curing agent B was used to replace the modified amine epoxy curing agent A in Example 1.
[0134] The remaining materials and amounts are the same as those in Example 1 to obtain a tile caulking agent.
[0135] Test Case
[0136] The shear bonding strength, compressive strength, stain resistance and afterglow brightness of the tile caulking agent prepared in the example were tested with reference to the provisions of CT 547-2017, JCT 1004-2017, JGT 463-2014 and GBT 24981.2-2020 standards. The experimental results are shown in Table 3 (Examples 1-6 and Comparative Examples 1-4 in the table are the prepared tile caulking agents respectively).
[0137] Table 3
[0138]
[0139]
[0140] It can be seen from the results in Table 3 that the tile caulking agent prepared by the present invention has the characteristics of shear bonding strength, compressive strength and high afterglow brightness.
[0141] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A raw material composition for tile caulking agent, characterized in that: The composition contains combination A and combination B in a weight ratio of 1:0.8-1.2; Based on the total mass of the A combination, the A combination contains: 80-90wt% epoxy resin, 5-10wt% nano calcium carbonate, 1-3wt% defoamer, 1-10wt% active diluent, and 1-10wt% luminous powder; Based on the total mass of the B combination, the B combination contains: 70-80wt% of modified amine epoxy curing agent, 5-10wt% of nano calcium carbonate, 1-3wt% of thixotropic agent, 1-3wt% of accelerator, 1-10wt% of toughening agent, 1-3wt% of defoaming agent, 1-10wt% of luminous powder, and 0-10wt% of pigment; In the combination A, the epoxy resin is a combination of bisphenol A epoxy resin and hydrogenated bisphenol A epoxy resin, and the amounts of the bisphenol A epoxy resin and the hydrogenated bisphenol A epoxy resin are such that the epoxy equivalent of the epoxy resin in the combination A is 180-190 g / mol; In the B combination, the active hydrogen equivalent of the modified amine epoxy curing agent is 170-180 g / mol; In the combination A and the combination B, the average volume diameter of the nano-calcium carbonate particles is 0.01 μm-0.1 μm.
2. The composition according to claim 1, characterized in that In the A combination, the weight ratio of the bisphenol A epoxy resin to the hydrogenated bisphenol A epoxy resin in the epoxy resin is 2-3:1; And / or, in the combination A and the combination B, the luminous powder is each independently yellow-green luminous powder and / or blue-green luminous powder, and the average volume diameter of the particles of the luminous powder is ≤50 μm.
3. The composition according to claim 1 or 2, characterized in that In the combination A, the active diluent is at least one of 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and polypropylene glycol diglycidyl ether; Preferably, in the combination A, the active diluent is 1,6-hexanediol diglycidyl ether.
4. The composition according to any one of claims 1 to 3, characterized in that In the combination B, the thixotropic agent is a polyamide solution; And / or, in the combination B, the accelerator is a tertiary amine accelerator; And / or, in the combination B, the toughening agent is amino-terminated liquid nitrile rubber.
5. A method for preparing a tile caulking agent, characterized in that: The method is carried out using the components in the composition according to any one of claims 1 to 4, comprising: (1) Preparation of the first component and the second component: Under stirring conditions, the components in combination A are first mixed to obtain a first component; and, Under stirring conditions, the components in combination B are mixed for a second time to obtain a second component; (2) The first component and the second component are mixed and contacted to obtain the tile grout.
6. The method according to claim 5, characterized in that In step (1), the operation of first mixing the components in combination A under stirring conditions includes: (S11) performing a first stirring treatment on a bisphenol A epoxy resin and a hydrogenated bisphenol A epoxy resin to obtain a material S11; (S12) at a temperature of T1, subjecting the material S11 to a second stirring treatment with the active diluent in combination A, the defoaming agent in combination A, and the nano-calcium carbonate in combination A, to obtain material S12; the temperature T1 being 40-50° C.; (S13) subjecting the material S12 and the luminous powder in combination A to a third stirring treatment to obtain the first component.
7. The method according to claim 6, characterized in that In step (S11), the conditions of the first stirring treatment include: a stirring rate of 400-600 rpm; And / or, in step (S12), the conditions of the second stirring treatment include: a stirring rate of 900-1000 rpm, a stirring time of 25-35 min, and a pressure ≥-0.09 Mpa; And / or, in step (S13), the conditions of the third stirring treatment include: a stirring rate of 400-600 rpm and a stirring time of 10-20 min.
8. The method according to claim 5, characterized in that In step (2), the operation of subjecting the components in combination B to a second mixing under stirring conditions includes: (S21) at a temperature of 45-50° C., the modified amine epoxy curing agent, the accelerator, the toughening agent, the defoaming agent in the combination B, and the nano-calcium carbonate in the combination B are subjected to a fourth stirring treatment to obtain material S21; the temperature T2 is 45-50° C.; (S23) subjecting the material S21, the thixotropic agent, the luminous powder in the combination B, and the pigment optionally contained in the combination B to a fifth stirring treatment to obtain the second component.
9. The method according to claim 8, characterized in that In step (S21), the conditions of the fourth stirring treatment include: a stirring rate of 900-1000 rpm, a stirring time of 25-35 min, and a pressure ≥ -0.09 Mpa; And / or, in step (S22), the conditions of the fifth stirring treatment include: a stirring rate of 400-600 rpm and a stirring time of 10-20 min.
10. A tile grout prepared by the method according to any one of claims 5 to 9.
Citation Information
Patent Citations
Two-component adhesive and preparation method thereof
CN106047258A
Double-component epoxy resin-based joint mixture
CN109679554A
Mildew-proof sealant and preparation method thereof
CN116285822A
Epoxy adhesive as well as preparation method and application thereof
CN117820998A
Hydrogenated epoxy floor paint and preparation method thereof
CN117844344A
Cited By
Joint filling glue material without sagging on vertical surface and preparation method thereof
CN121160277A